Physiological and ultrastructural characterisation of a desiccation‐tolerant filmy fern, Hymenophyllum caudiculatum: Influence of translational regulation and ABA on recovery. (28th November 2017) - Garcés, M.; Ulloa, M.; Miranda, A.; Bravo, L. A.
Abstract: The filmy fern Hymenophyllum caudiculatum can lose 60% of its relative water content, remain dry for some time and recover 88% of photochemical efficiency after 30 min of rehydration. Little is known about the protective strategies and regulation of the cellular rehydration process in this filmy fern species. The aim of this study was to characterise the filmy fern ultrastructure during a desiccation–rehydration cycle, and measure the physiological effects of transcription/translation inhibitors and ABA during desiccation recovery. Confocal and transmission electron microscopy were used to compare changes in structure during fast or slow desiccation. Transcription (actinomycin D) and translation (cycloheximide) inhibitors and ABA were used to compare photochemical efficiency during desiccation recovery. Cell structure was conserved during slow desiccation and rehydration, constitutive properties of the cell wall, allowing invagination and folding of the membranes and an important change in chloroplast size. The use of a translational inhibitor impeded recovery of photochemical efficiency during the first 80 min of rehydration, but the transcriptional inhibitor had no effect. Exogenous ABA delayed photochemical inactivation, and endogenous ABA levels decreased during desiccation and rehydration. Frond curling and chloroplast movements are possible strategies to avoid photodamage. Constitutive membrane plasticity and rapid cellular repair can be adaptations evolved to tolerate a rapid recovery during rehydration. Further research is required to explore the importance of existing mRNAs during the first minutes of recovery, and ABA function during desiccation of H. caudiculatum .